2021
DOI: 10.1038/s41379-021-00744-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent MEIS1-NCOA2/1 fusions in a subset of low-grade spindle cell sarcomas frequently involving the genitourinary and gynecologic tracts

Abstract: C. R. (2021). Recurrent MEIS1-NCOA2/1 fusions in a subset of low-grade spindle cell sarcomas frequently involving the genitourinary and gynecologic tracts. Modern Pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 19 publications
(24 reference statements)
1
50
3
Order By: Relevance
“…Eight unusual sarcomas have been reported harboring the same MEIS1‐NCOA2/1 gene fusion involving the urinary and gynecologic tract. These tumors were composed of monomorphic plump spindle cells arranged in vague fascicles with a whorling pattern, a primitive round cell component, and aggressive histological features 24,25 . Immunohistochemically, a minority of these tumors were very focally positive for desmin and all were negative for myogenin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight unusual sarcomas have been reported harboring the same MEIS1‐NCOA2/1 gene fusion involving the urinary and gynecologic tract. These tumors were composed of monomorphic plump spindle cells arranged in vague fascicles with a whorling pattern, a primitive round cell component, and aggressive histological features 24,25 . Immunohistochemically, a minority of these tumors were very focally positive for desmin and all were negative for myogenin.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors were composed of monomorphic plump spindle cells arranged in vague fascicles with a whorling pattern, a primitive round cell component, and aggressive histological features. 24,25 Immunohistochemically, a minority of these tumors were very focally positive for desmin and all were negative for myogenin. The relationship of these undifferentiated tumors to SpRMS with MEIS1-NCOA2 gene fusions is unclear.…”
Section: Agaram Et Al Recently Characterized Seven Primary Intraosseousmentioning
confidence: 99%
“…MEIS1-NCOA2 fusion-positive low grade spindle cell tumors also occur in the genitourinary and gynecological tracts and again mostly affect adults; both RMS and non-RMS cases are described. 66…”
Section: Current Understanding Of the Molecular Basis Of Rmsmentioning
confidence: 99%
“…MEIS1-NCOA2 fusion-positive low grade spindle cell tumors also occur in the genitourinary and gynecological tracts and again mostly affect adults; both RMS and non-RMS cases are described. 66 A single paper describes a distinct type of welldifferentiated SCRMS with SRF-FOXO1 or SRF-NCOA1 fusions. 67 The authors describe only three cases were reported, all deep paraspinal tumors in young children.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in zebrafish models, vgll2a is required for neural crest cell survival and craniofacial development 12 . NCOA2 is a common 3' fusion partner in non-spindle cell sarcoma contexts; examples including HEY1-NCOA2 in mesenchymal chondrosarcoma, MEIS1-NCOA2 in genitourinary and gynecologic tract spindle cell sarcomas and intraosseous rhabdomyosarcomas, and PAX3-NCOA2 in alveolar rhabdomyosarcoma [13][14][15][16][17] . Suggestively, TEAD1-NCOA2 fusions have also been identified in infantile rhabdomyosarcoma, indicating converging developmental processes for this subtype 18,19 .…”
Section: Introductionmentioning
confidence: 99%